A taxonomic review of the genus Antodynerus de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from the Indian subcontinent - Kumar, Girish P.; Carpenter, James M. (Zootaxa, 2013)
The genus Antodynerus de Saussure, 1855 is reviewed from the Indian subcontinent. Three species with one additional subspecies are present, namely Antodynerus flavescens flavescens (Fabricius, 1775), A. f. karachiensis Giordani Soika, 1970, A. limbatus (de Saussure, 1852), and A. punctatipennis (de Saussure, 1853). The parasitic association of strepsipteran insects and the symbiotic association of mites are reported for the first time in the genus Antodynerus. The distribution of A. f. flavescens (Fabricius) and A. limbatus (de Saussure) in the Indian states is augmented. The latter species is newly recorded from China (Tibet). A key to species of the Indian subcontinent is provided.